Pengetahuan Pelajar Unisza Terhadap Istilah Bahasa Arab Dalam Bidang Fikah - Tengku Fatimah Muliana, Tengku Muda; Syh Noorul Madihah, Syed Husin; Sumayyah, Abdul Aziz (2014)
Arabic language is significant especially in the discipline of fiqh which is among the keys to the study of religion. The terms used in the discipline of fiqh by Islamic scholars are derived from the Arabic terminology of the Quran, the Hadith, or Ijtihad of the Companions, or of the tabi'in. Developments of fiqh literature show that these terms are still mostly preserved in Arabic. Hence the scholar’s knowledge of Arabic terminology will have an impact on the understanding and application of the knowledge of fiqh. Therefore, based on the importance of understanding the Arabic terminologies, a brief study is conducted among diploma students of University of Sultan ZainalAbidin (UniSZA) on Arabic terms commonly used in the field of fiqh. It is to analyze their level of knowledge in three selected areas of fiqh namely purification, prayer and fasting. It is also to identify the terms least acknowledged by the respondents in such areas. This article also aimed at comparing the achievement between students with religious background as compared to non religious background. A set of performance test questions were distributed to 269 randomly selected samples. The data were analyzed descriptively based on three areas of fiqh by focusing on the frequency of knowledge of respondents for each item, the percentage and the mean score in each area as well as overall. The result of religious and non- religious stream respondents will also be analyzed descriptively through cross tabulation. The results showed a mean score for all items tested was 54.81%. This shows that the respondents’ knowledge of the Arabic terms in Islamic fiqh is only average. Comparison of mean scores between the three area of fiqh shows that the Arabic term of purification is the least known term by the respondents with the mean score of 40.26 % , compared to prayer (56.25%) and fasting (67.92%) . The study also shows that students with religious school background have better knowledge than those from the non- religious school background.